Moskiewska „czernucha”. Wstydliwa strona miasta? - Zywert, Aleksandra (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article is an attempt to answer the question of the way noir functions in the contemporary prose devoted to Moscow and the extent to which it affects the city’s literary image. The paper interprets selected works by Vladimir Sorokin, Roman Senchin and Sergei Kuznetsov. The analysis conducted by the author of the paper leads to the conclusion that the presence of the so-called “black naturalism” in the Moscow texts does not spoil the image of Russia’s capital, but complements it with new elements (previously hidden, but present since the old days). Therefore, Moscow becomes more real, tangible, flesh and blood as well as suitable for the worldwide tendency to create megapolises.